2000
DOI: 10.1099/00221287-146-1-199
|View full text |Cite
|
Sign up to set email alerts
|

Three pathways for trehalose biosynthesis in mycobacteria

Abstract: Trehalose is present as a free disaccharide in the cytoplasm of mycobacteria and as a component of cell-wall glycolipids implicated in tissue damage associated with mycobacterial infection. To obtain an overview of trehalose metabolism, we analysed data from the Mycobacterium tuberculosis genome project and identified ORFs with homology to genes encoding enzymes from three trehalose biosynthesis pathways previously characterized in other bacteria. Functional assays using mycobacterial extracts and recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
226
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(230 citation statements)
references
References 37 publications
2
226
0
Order By: Relevance
“…The physiological role of the multiple pathways associated with trehalose metabolism has been unequivocally established in a few bacteria only (De Smet et al, 2000;Wolf et al, 2003;Makihara et al, 2005). Firm evidence for the role of TreS in trehalose degradation has been obtained with mutants of Rhodobacter sphaeroides (Makihara et al, 2005), and a similar function for TreS has been proposed in C. glutamicum.…”
Section: Discussionmentioning
confidence: 72%
“…The physiological role of the multiple pathways associated with trehalose metabolism has been unequivocally established in a few bacteria only (De Smet et al, 2000;Wolf et al, 2003;Makihara et al, 2005). Firm evidence for the role of TreS in trehalose degradation has been obtained with mutants of Rhodobacter sphaeroides (Makihara et al, 2005), and a similar function for TreS has been proposed in C. glutamicum.…”
Section: Discussionmentioning
confidence: 72%
“…An enzymic trehalose determination assay was used which was based on the quantitative hydrolysis of trehalose to two molecules of glucose, using recombinant trehalase from E. coli. For this purpose, the E. coli trehalase TreA was overexpressed and partially purified as described by De Smet et al (2000). Samples of 5-20 ml were incubated with or without recombinant trehalase (5 U) in 90 ml 10 mM sodium/potassium phosphate buffer pH 6?0 for 1 h at 37 uC.…”
Section: Methodsmentioning
confidence: 99%
“…Strains of this genus have been shown by in vitro assays to possess all three pathways for trehalose synthesis (De Smet et al, 2000). The question arises as to what biological role trehalose has in these bacteria that makes necessary a threefold coverage of its biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems unlikely that glycogen in this organism serves as a long-term carbon storage compound, and in fact, glycogen metabolism in C. glutamicum has previously been suggested to be important for trehalose synthesis (Padilla et al, 2004;Seibold et al, 2007;Tzvetkov et al, 2003;Wolf et al, 2003). It has been shown that linear maltodextrins (formed as intermediates during glycogen synthesis and degradation) serve as substrates for the two-step trehalose biosynthetic pathway via maltooligosyltrehalose synthase (TreY) and maltooligosyltrehalose trehalohydrolase (TreZ) (Carpinelli et al, 2006;De Smet et al, 2000). Since trehalose in C. glutamicum acts as a cell-wall component (Tropis et al, 2005) and as a compatible solute under hyperosmotic and nitrogen-limitation conditions (Wolf et al, 2003), glycogen degradation and its control might be important for the cell-wall composition and for the response to osmotic stress in this organism.…”
Section: Introductionmentioning
confidence: 99%